Karakteristik Kepribadian Frater di Wilayah Keuskupan Agung Jakarta Berdasarkan Five-Factor Model - Guiedo Hendy Indra; Magdalena S. Halim (MANASA, 2021)
Personality is one of the main things that are being shaped during the formation of Catholic Priest. However, assessments of personality are often only based on preceptor observations. This study aims to find out the personality characteristics of the brothers to help the preceptors educating them. This research is a quantitative descriptive study with 82 brothers who live in Archdiocese of Jakarta as participants. Participants are currently undergoing stage of Bachelor studies, Pastoral Orientation Year, or Master studies with age range of 20-38 years (M = 23.44, SD = 3.447). Participants were collected by convenience sampling method, by distributing online questionnaires. The general personality description is obtained by processing the score of each Big Five Marker (IPIP-BFM-50) in Indonesian domain with descriptive statistical methods. ANOVA test is carried out to see the differences based on the formation stages. Most of the brothers have moderate scores for each domain, so the expressions can be trained to suit the needs of Church. However, some of them have extremely low score on Emotional Stability (3.7%), thus showing high tendency to be susceptible to stress and negative emotions. Agreeableness is the dominant characteristic as there are no extreme low scores in this domain and the SD on the raw score is also the smallest. It is also found that there are significant differences in Agreeableness based on the stages of the formation that are being undertaken.